2014
DOI: 10.1124/jpet.114.218370
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Galectin-3 and Its Role in Fibrotic Diseases

Abstract: Fibrotic diseases occur in a variety of organs and lead to continuous organ injury, function decline, and even failure. Currently effective treatment options are limited. Galectin-3 (Gal-3) is a pleiotropic lectin that plays an important role in cell proliferation, adhesion, differentiation, angiogenesis, and apoptosis. Accumulating evidence indicates that Gal-3 activates a variety of profibrotic factors, promotes fibroblast proliferation and transformation, and mediates collagen production. Recent studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
195
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(207 citation statements)
references
References 88 publications
(124 reference statements)
4
195
1
7
Order By: Relevance
“…В их числе наиболее перспективным является представитель семейства галектинов -галектин-3 (Гал-3) [6], который прини-мает участие во многочисленных физиологических процессах на молекулярном уровне [7]. Повышение его концентрации в сыворотке крови и в тканях отмечено при разнообразной, в том числе, и при кар-диальной патологии, сопровождающейся развитием фиброза [8], а также диастолической дисфункции миокарда [9].…”
Section: обоснование исследованияunclassified
See 1 more Smart Citation
“…В их числе наиболее перспективным является представитель семейства галектинов -галектин-3 (Гал-3) [6], который прини-мает участие во многочисленных физиологических процессах на молекулярном уровне [7]. Повышение его концентрации в сыворотке крови и в тканях отмечено при разнообразной, в том числе, и при кар-диальной патологии, сопровождающейся развитием фиброза [8], а также диастолической дисфункции миокарда [9].…”
Section: обоснование исследованияunclassified
“…НАЖХП часто поєднується з гіпергомоцисте-їнемією (ГГЦ), яку розглядають як патогенетичний чинник акселерації печінкового стеато-та фіброге-незу у хворих на хронічні вірусні гепатити [5]. Пору-шення обміну метіоніну, дефіцит вітамінів групи В та фолієвої кислоти сприяють розвитку карнітинової недостатності та ектопії жирів у печінці [6].Нещодавно встановлено, що розвиток стеатозу та фіброзу печінки може асоціюватись з порушенням продукції таких медіаторів як гідроген сульфід (Н 2 S) [7,8] та інсуліноподібний фактор росту-1 (IGF-1) [9]. 9.…”
unclassified
“…Galectin-3, a member of the β-galactoside-binding galectin family, is uniquely chimeric (Ahmed & AlSadek, 2015;de Oliveira et al, 2015). Originally, galectin is found to be involved in multiple aspects, including cell adhesion, proliferation, clearance, apoptosis, cell activation, cell migration, and phagocytosis (Li, Li, & Gao, 2014;Peacock & DiSomma, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Gal-3 is a multifunctional adhesion-modulated and growthregulatory β-galactoside-binding lectin that secreted by activated mononuclears / macrophages and contributed to various pathophysiological processes affected cardiac / vascular remodeling, cardiac fibrosis, and inflammation [17]. As a multifactorial regulator of cell function Gal-3 is involved in cell proliferation / differentiation, angiogenesis, neovascularization, as well as malignancy, tumor cell adhesion and metastasis [18].…”
Section: The Biological Role and Function Of Galectin-3mentioning
confidence: 99%
“…Recent pre-clinical and clinical studies have been indicated an important role for Gal-3 signaling mechanism in the pathophysiology of IPAH and PAH-CTD [15,16]. Moreover, Gal-3 acts a fundamental regulator of inflammation, fibrosis, angiogenesis, adhesion, tumor growth and progression, and immunological functions [17][18][19]. There is evidence regarding independent association between Gal-3 levels and microalbuminuria, an early marker of endothelial dysfunction and altered renal function [20].…”
Section: Introductionmentioning
confidence: 99%